2011
DOI: 10.2165/11586450-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Managing Suicide Risk in Patients with Schizophrenia

Abstract: The management of suicide risk in patients with schizophrenia poses many challenges for clinicians. Compared with the general population, these patients have an 8.5-fold greater risk of suicide. This article reviews the literature dealing with the treatment of at-risk patients with schizophrenia. An integrated psychosocial and pharmacological approach to managing this population of patients is recommended. Although there is at least modest evidence suggesting that antipsychotic medications protect against suic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
93
1
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(102 citation statements)
references
References 126 publications
2
93
1
3
Order By: Relevance
“…The evidence supports a clear advantage of clozapine therapy in terms of reduced mortality over other antipsychotic agents including FGAs, risperidone and quetiapine [39][40][41][42].…”
Section: Clozapine Effectiveness On Mortalitymentioning
confidence: 68%
See 1 more Smart Citation
“…The evidence supports a clear advantage of clozapine therapy in terms of reduced mortality over other antipsychotic agents including FGAs, risperidone and quetiapine [39][40][41][42].…”
Section: Clozapine Effectiveness On Mortalitymentioning
confidence: 68%
“…It has also been suggested that earlier use (as a second line agent) can be recommended in individuals with persistent hostility/aggressive behaviour [47] and suicidalilty [39][40][41][42]. In fact the indication for recurrent suicidal behavior has been officially approved by the FDA [48].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from depression, the other psychiatric condition which shares this symptom and contributes significantly to the number of suicides committed is schizophrenia [112]. However, pharmacotherapy of suicidal ideation/behaviour is still premature.…”
Section: Pharmacological Management Of Suicidal Ideationmentioning
confidence: 99%
“…It implies different prescription habits linked to differences in psychiatric training provisions in the two countries. More generally, data on the utility of antipsychotics in reducing risk for suicide in patients with schizophrenia are, although appreciably favorable, still limited, except for clozapine, the only antipsychotic treatment approved by the Food and Drug Administration for this indication (Kasckow et al, 2011;Meltzer et al, 2003).…”
Section: Factors Favoring the Prescription Of Depot Formsmentioning
confidence: 99%